Case report: Diagnostic and therapeutic challenges of fungal endocarditis by Trichosporon asahii in a child with congenital heart defects - Baptistella, Amanda; Rossato, Ana Júlia A.; de Gusmão, Beatriz C.; Cunha, Carolina M.; Trafane, Luiza F.; Colbachini, Paulo C. M. (Frontiers in Pediatrics, 2023)
Background: patients with congenital cardiopathies are the main group at risk for infective endocarditis (IE) in the pediatric population. Fungal etiology is responsible for 2-4% of all IEs, and the Trichosporon genus is an increasingly prevalent cause of infections in human beings. Case presentation: We describe a 9-year-old male with multiple surgical procedures to correct congenital cardiopathy defects, including insertion of RV-PA conduit, who was admitted due to suspicion of pneumonia and needed a surgical approach after being diagnosed with a mycotic pseudoaneurysm in the right ventricle's outflow tract, with dilation of the RV-PA conduit. The conduit was removed and antifungal treatment was started with Voriconazole after the agent was identified (T. asahii), with satisfactory therapeutic response. Approximately 4 years later, the patient was readmitted, presenting with intermittent fever, associated with nocturnal diaphoresis, dry cough, anxiety and chest pain.Vegetations consistent with T. asahii were evidenced in the RV-PA conduit, and a surgical approach This is a provisional file, not the final typeset article was once again necessary. Discussion: diagnostic methods and treatment of T. asahii endocarditis aren't yet standardized, and recurrent surgical approaches are needed due to the inefficacy of antifungal treatment.